Rebuilding Ukraine with a Resilient, Carbon-Neutral Energy System - United Nations Economic Commission for Europe (United Nations, 2023)
This study, prepared by UNECE experts, builds upon UNECE’s work on Building Resilient Energy Systems and utilizes the UNECE Carbon Neutrality Toolkit. The analysis presented here focuses on a carbon-neutral scenario for the post-war restoration of Ukraine's energy system. The findings aim to serve as a valuable source and tool for future horizon scanning efforts and broader foresight processes to support policymaking. The objective is to assist the Ukrainian government in exploring different pathways and rebuilding its energy system based on the concept of carbon neutrality. Ukraine continues to heavily rely on fossil fuels, accounting for 70% of its Total Primary Energy Supply (TPES) in 2020. The Russian invasion of Ukraine had a significant impact on the energy sector, resulting in a 43% drop in energy demand in 2022 compared to 2013.